(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Communication envisages the consideration of parliament as a platform for dialogue between government agencies, civil society, political parties and social movements to improve the efficiency of their work, taking into account and the greatest coverage of public opinion. An article about the political system in Kyrgyzstan.